General Dynamic Modeling of a Scissor Structure for its Deployment Control in Space. Issue 3 (December 2015) - Takatsuka, Masao
The objective of the present study is to reveal a dynamic calculation method for a deployable scissor structure in space as an unstable structure without boundaries, by generalizing its dynamic modeling to predict the relationship between its deployment motion and input moment generated by an actuator. The purpose is to study the construction process of space structures such as a solar power satellite in future. Whereas our previous study demonstrated a specific derivation sequence of a dominant equation of a scissors unit, the present paper shows the generalized derivation sequence and its numerical calculation examples of more extended analysis models.